2016
DOI: 10.1186/s12885-016-2912-y
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Her2/neu expression in colorectal adenocarcinoma: a study from developing South Asian Country

Abstract: BackgroundHuman Epidermal Growth Factor (Her-2/neu) has strong therapeutic implications in certain cancers like breast and gastric cancer. Literature on its frequency in colorectal cancer is scarce. In this study, we have investigated the frequency of Her-2/neu expression in colorectal adenocarcinomas and its association with various clinicopathological variables.MethodsA total of 95 patients who underwent colonoscopic biopsy or colectomy were studied after Institutional Ethical Approval. Hematoxylin & eosin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…did not find any significant correlation between the stage of tumors and the expression of HER2/neu [35], but Shabbir et al find such a correlation [33].…”
Section:  Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…did not find any significant correlation between the stage of tumors and the expression of HER2/neu [35], but Shabbir et al find such a correlation [33].…”
Section:  Discussionmentioning
confidence: 92%
“…HER2/neu is a proto-oncogene located on chromosome 17q21 that encodes ErbB-2, a 185-kDa transmembrane tyrosine kinase receptor. HER2 gene amplification and overexpression of HER2/neu has been associated with pathogenesis and progression of several human cancers [33].…”
Section:  Discussionmentioning
confidence: 99%
“…CRC is associated in 60% of tumors with BRAF mutation and BRAF is the downstream of HER2 protein [7]. Previous studies have reported that the HER2 expression was significantly correlated with tumor size, histological differentiation, lymph node metastases, and tumor stage [25][26][27][28]. In contrast to these studies, other researchers have found no such association [29,30].…”
Section: Discussionmentioning
confidence: 90%
“…Her-2 over expression in colorectal cancer is quite debatable, showing a wide range of variability (0-83%) [7]. Some studies reported only membranous Her-2 over expression while others reported membranous as well as cytoplasmic expression [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%